Odonata diversity of the Kuruva Islands, southern India, with notes on the ecology of Disparoneura apicalis (Fraser, 1924) (Odonata: Platycnemididae) - Ayikkara Vivek Chandran; Puthukudy Kunjamu Muneer; Maran Madhavan; Subin Kaniyamattathil Jose (Journal of Insect Biodiversity and Systematics)
Odonata diversity of the Kuruva Islands in Wayanad, a part of the Western Ghats Biodiversity Hotspot in southern India, was studied for a year using transect counts. A total of 59 species were recorded of which 7 are endemic to the Western Ghats. Herb cover, shrub cover, open space, water pH, air temperature, and a composite water chemistry variable incorporating conductivity, TDS, and salinity emerged as the most important predictors of Odonata diversity. The distribution of the endemic and Vulnerable Disparoneura apicalis (Fraser, 1924) in the islands is influenced by particular species of plants that act as their perching posts and ovipositing sites. It is recommended that the tourists visiting the Kuruva Islands be sensitized about the importance of the place as an odonate habitat. The highly range-restricted D. apicalis can be made a flagship species for the conservation of this unique ecosystem.